Resposta da função autonômica, transporte mucociliar e potência aeróbia máxima de pacientes com doença pulmonar obstrutiva crônica submetidos a um treinamento aeróbio - Leite, Marceli Rocha [UNESP] (2014)
The effects of physical training are well established in chronic obstructive pulmonary disease (COPD), it is an essential and mandatory part in pulmonary rehabilitation programs. However, despite the many benefits provided by performing physical exercises, information regarding cardiac autonomic modulation during and after an acute bout of aerobic exercise as well as the influence of a periodization aerobic training in autonomic modulation, mucociliary clearance and aerobic power in COPD is unknown. Aims: This work aimed to evaluate the acute response of cardiac autonomic modulation during and after one session of aerobic exercise in patients with COPD, in addition to analyze the influence of a periodized exercise training in autonomic modulation, and mucociliary transport and aerobic power in patients with COPD. Methods: The experimental protocol for analysis of the acute response of the autonomic modulation was composed by a session of aerobic exercise equivalent to 60% and 90% of velocity corresponding to peak oxygen consuption (vVO2peak). For the analysis of heart rate variability (HRV)...